Assessment of nutritional status and its associated factors among people affected by human immune deficiency virus on antiretroviral therapy: a cross sectional study in Siltie zone, south Ethiopia - Mewuba Shamil Saliya; Telake Azale; Atinkut Alamirew; Dawit Jember Tesfaye (PAGEPress Publications, 2018)
Ethiopia is among the countries most affected by malnutrition and nutrition-related complications remain a challenging issue for Human Immunodeficiency Virus (HIV)- infected patients and those involved in their care. The aim of this study was to assess nutritional status among HIV positive adults in South Ethiopia and assess risk factors for malnutrition in this population. Institution based cross sectional study was conducted among 428 HIV positive adults who are taking ART at 12 health centers, Silte zone, Ethiopia. Convenience sampling technique was used to select the study participants. Structured questionnaire and anthropometric measurements were used to collect data. Data were analyzed using SPSS version 20.0 software. Bivariate and multivariate analyses were used to identify predictors of malnutrition. P-value less than 0.05 were used as cut of point to declare statistical significance. Prevalence of chronic energy deficiency was 24.1%. Food insecurity [AOR= 0.35, 95% CI (0.21, 0.62)], feeding ≤ 2 meals/day [AOR= 0.29, 95% CI (0.29, 0.13)], ambulatory functional status [AOR= 3.4, 95% CI (1.67, 6.98)] and absence of dietary counseling [AOR= 1.7, 95% CI (1.05, 2.78)] were found to be independent predictors of chronic energy deficiency among HIV positive adults. Prevalence of malnutrition is high among HIV infected adults who are on ART in the study area. Regular nutritional assessment of the patients and dietary counseling should be integrated with routine care for HIV/AIDS patients. HIV/AIDS prevention and control programs need to involve nutritionists or trained health care provider to integrate nutritional care services.